Evaluation of allergic diseases, symptom control, and relation to infections in a group of Italian elite mountain bikers - Perrotta, F.; Simeon, V.; Bonini, M.; Ferritto, L.; Arenare, L.; Nigro, E.; Nicolai, A.; Daniele, A.; Calabrese, C. (Clinical Journal of Sport Medicine, 2020)
Objectives: This study estimates the prevalence of allergic diseases in a group of Italian elite mountain bikers, compares the prevalence of infectious episodes between allergic and nonallergic athletes, and evaluates asthma and rhinitis symptom control in allergic athletes. Design: Two hundred twenty-six Italian nonsmoking mountain bikers received by mail the Allergy Questionnaire for Athletes (AQUA) and completed it. The RhinAsthma Patient Perspective (RAPP) questionnaire was sent to the 108 participants with a positive AQUA score and 104 returned the questionnaire. Methods: Athletes with an AQUA score =5 or <5 were defined AQUA+ (allergic) or AQUA- (nonallergic), respectively. RhinAsthma Patient Perspective questionnaire total score =15 was indicative of a poor control of symptoms. Results: Of the 226 athletes, 47.8% were AQUA+, whereas 52.2% were AQUA-. A higher number of AQUA+ athletes reported frequent upper respiratory tract infections (URTIs) and herpes labialis than AQUA- athletes (P < 0.001), and the prevalence of URTI was greater in the subgroup of AQUA+ athletes who trained =3 hours per session. According to RAPP questionnaire score, 21.1% of AQUA+ mountain bikers had a poor control of asthma and rhinitis symptoms. Conclusions: Our study shows a high prevalence of allergy among Italian elite mountain bikers whose asthma and rhinitis symptoms are poorly controlled in about a fifth of the sample. Allergic athletes, mainly those training more than 3 hours per session, are at higher risk of URTI and herpes labialis. Screening programs to detect allergic diseases and to evaluate symptom control in athletes should be strongly encouraged.